THE TEACHERS’ STRATEGIES TO INSTILL MORALS IN STUDENTS OF STATE JUNIOR HIGH SCHOOL 3 BONTOMATENE - B, Muhammad Rusmin; Damopolii, Muljono (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aimed to map the form of moral instilling activities, identify the various obstacles teachers face, and determine the teachers’ strategies. This research used the qualitative descriptive method. The data sources of this research were the principal, vice-principal, two teachers, and students. The data used were documents and interviews collected through observation, interviews, and documentation. The data were analyzed by inductive analysis technique. The results indicated that: 1) there were two forms of activities of moral instilling to students, habituation and exemplary. 2) The obstacles came from various sources such as parents, the community environment, or the students themselves. The obstacles include smartphone usage, lack of discipline, and lack of parental roles. 3) The teachers’ strategies in instilling morals in students were direct and indirect approaches. The direct approach could be through speech and deeds, and the indirect approach could be through mentoring. Abstrak: Penelitian ini bertujuan untuk memetakan bentuk kegiatan penanaman akhlak, mengidentifikasi berbagai kendala yang dihadapi guru, dan menentukan strategi guru. Penelitian ini menggunakan metode deskriptif kualitatif. Sumber data penelitian ini adalah kepala sekolah, wakil kepala sekolah, dua orang guru, dan siswa. Data yang digunakan adalah dokumen dan wawancara yang dikumpulkan melalui observasi, wawancara, dan dokumentasi. Data dianalisis dengan teknik analisis induktif. Hasil penelitian menunjukkan bahwa: 1) terdapat dua bentuk kegiatan penanaman akhlak kepada siswa, yaitu pembiasaan dan keteladanan. 2) Berbagai kendala yang dihadap datang dari berbagai sumber seperti orang tua, lingkungan masyarakat, atau siswa itu sendiri. Kendala tersebut antara lain penggunaan smartphone, kurangnya disiplin, dan kurangnya peran orang tua. 3) Strategi guru dalam menanamkan akhlak pada siswa adalah pendekatan langsung dan tidak langsung. Pendekatan langsung dapat dilakukan melalui ucapan dan perbuatan, dan pendekatan tidak langsung dapat melalui pendampingan.